ANALYSIS OF NON-OPTIMAL PV SIZING AND PLACEMENT IN DISTRIBUTION NETWORKS WITH COMMERCIAL, INDUSTRIAL, AND RESIDENTIAL LOADS (Jurnal Teknologi (Sciences & Engineering), 2025)
The integration of Photovoltaic (PV)-based Distributed Generation (DG) into distribution networks is significantly influenced by varying load consumption patterns. Commercial, industrial, and residential users exhibit distinct consumption profiles, which impact the demand-supply dynamics within these networks. Therefore, implementing an effective optimization method to determine the optimal size and location of PV systems in the distribution network, while considering varying load patterns, is crucial for optimizing energy production, reducing dependence on the grid, and minimizing power losses. An optimization approach using Particle Swarm Optimization (PSO) is proposed to address this challenge effectively. To verify the effectiveness of the proposed method, simulation studies were conducted on IEEE 33 bus test distribution networks. Various test cases were examined to investigate the impacts of improper PV sizing and placement, and the results were compared with those of the proposed method. The findings revealed that the optimal placement and sizing of PV systems, as determined using PSO, achieved power loss reductions of 13.84%, 20.70%, and 32.71% for industrial, residential, and commercial loads, respectively, when located at bus 6. In contrast, improper PV installation resulted in either excess or insufficient power generation, leading to higher power losses and inefficiencies within the system.